Решите уравнения: е) (2)/(x-5) - (4)/x+5=3/x^2-25 ж) 4/(y-2)-2/y=(3-y)/(y^2-2y) з) 1/(x-2)^2+9/(x+2)^2-6/(x^2-4)=0

exampllee1 exampllee1    1   21.09.2019 16:10    0

Ответы
Katya124354 Katya124354  08.10.2020 07:31
(2)/(x-5) - (4)/(x+5)=3/(x^2-25)
общий знаменатель ( x - 5 )( x + 5 ) = x^2 - 25 
x ≠ 5 ; x ≠ - 5 
2( x + 5 ) - 4( x - 5 ) = 3 
2x + 10 - 4x + 20 = 3
- 2x = 3 - 30 
x = 27/2 
x = 13,5

4/(y-2)-2/y=(3-y)/(y^2-2y)
общий знаменатель y( y - 2 ) = y^2 - 2y 
y ≠ 0 ; y ≠ 2 
4y - 2( y - 2 ) = 3 - y 
4y - 2y + 4 = 3 - y 
2y + y = 3 - 4 
3y = - 1 
y = - 1/3 

1/(x-2)^2+9/(x+2)^2-6/(x^2-4)=0 
общий знаменатель ( х - 2 )^2*( x + 2 )^2 
x ≠ 2 ; x ≠ - 2 
( x + 2 )^2 + 9( x - 2 )^2 - 6( x - 2 )( x + 2 ) = 0 
x^2 + 4x + 4 + 9( x^2 - 4x + 4 ) - 6( x^2 - 4 ) = 0
x^2 + 4x + 4 + 9x^2 - 36x + 36 - 6x^2 + 24 = 0 
4x^2 - 32x + 64 = 0 
( 2x - 8 )^2 = 0 
2x - 8 = 0 
x = 8 : 2 
x = 4 
ПОКАЗАТЬ ОТВЕТЫ